PERAN MEDIA GAME EDUKASI WORDWALL DALAM PEMBELAJARAN MODEL DISCOVERY LEARNING PERUBAHAN WUJUD BENDA SISWA SEKOLAH DASAR - Fauziyah, Risa; Achmad Fanani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is in the background because of the lack of student activity in learning activities and is a problem in the learning process in the classroom because students are an important indicator in the effective learning process. This is because teachers tend to use conventional methods and lack in utilizing learning media. The purpose of this study is to increase the activeness and understanding of the material of the Change of Form of Elementary School students in the learning process. This study uses a type of quantitative research with a